URBAN FARMING SISTEM WOLKAPONIK SEBAGAI SOLUSI KELANGKAAN CABAI RAWIT DI KOMPLEKS CICERI PERMAI - Hastutil, Dewi; Rohmawati, Imas; Romdhonah, Yayu (Jurnal Pengabdian Dinamika, 2018)
Cayenne pepper is currently a prima donna agricultural commodity. The price of cayenne pepper in the market ranges from 120,000 to 145,000 rupiah. The fluctuatife price of chilli is due to unbalanced demand with supply. In other words the amount of supply of cayenne pepper on the market is drastically reduced. Cayenne pepper is one of the spices that the level of demand in the market high because almost all dishes using this spice. This is due to the impact of the prolonged rainy season. Many farmers have failed to harvest cayenne pepper because the plants rot. The skyrocketing price of this spice happen to housewives in urban areas such as the Ciceri Permai Complex of Serang City. Solutions to overcome the high price of chili can be done with wolkaponik on the scale of the household. Wolkaponic is a modification between wallgardening and aquaponic technology. With its minimalist design, wolkaponic does not require a large area of land. Planting vegetables is done vertically and part at the bottom there is a fish pond (Savitri, 2014) .Wolkavonik is a multilevel cultivation way that consists of plants and fish ponds, so that the fish poop water can be utilized as fertilizer plants. Wolkaponik somewhat different from hydroponics . In the hydroponic system the main medium is water with added liquid nutrients. Nutrition commonly used is Abemix. Abemix must be obtained by buying in farm shops. Without these additional nutrients the hydroponic plants will not grow optimally. Wolkaponic systems are simpler to apply because nutrient sources do not necessarily have to buy. Sources of nutrients are available directly from the waste of fish that is fed to the plant media. In the medium wokaponic system is a mixture of zeolite and compost.The wolkaponic system is best suited to yard or urban housing land. This system can save space because it is designed in storied. Chili is grown in polybags or in pots without the need for soil. By applying this system, urban residents can still conduct agricultural cultivation or referred to as "urban farming". In addition to overcoming the high price of chili this system also has many other benefits. These benefits, among others, can improve the greening of the environment to beautify the landscape. In addition, wolkaponik also can clean the air because it donates oxygen to the air. With this system, urban residents can also meet their own protein needs by maintaining fish in portable ponds.